# Is this correct

-3a^2b/35a^5 * 14a^3b^2/-9b^4=
-42ab/-315a^5b^4

you need to simplify

_______________________________________

try again

*** i got

(2a^3)/(15b^2)

sorry i forgot something, looking back at my work

I now get

= 2 /(15b^2)

## To simplify the expression (-3a^2b/35a^5) * (14a^3b^2/-9b^4), we can follow these steps:

1. Combine the coefficients: -3 * 14 = -42.
2. Multiply the variables with the same base (a) and add their exponents: a^2 * a^3 = a^(2+3) = a^5.
3. Multiply the variables with the same base (b) and subtract their exponents: b * b^2 = b^(1+2) = b^3.
4. Simplify the expression by canceling out common factors: -42a^5b^3.

Thus, the simplified form of the expression is -42a^5b^3.

However, upon reviewing your work, I see that there was an error in your original calculation of the expression. The correct calculation is as follows:

(-3a^2b/35a^5) * (14a^3b^2/-9b^4) = (-3 * 14 * a^2 * a^3 * b * b^2) / (35 * -9 * a^5 * b^4)

Now, we can simplify the coefficients:
-3 * 14 = -42, and 35 * -9 = -315.

Next, let's simplify the variables:
a^2 * a^3 = a^(2+3) = a^5, and b * b^2 = b^(1+2) = b^3.

Finally, we cancel out common factors:
(-42 * a^5 * b^3) / (-315 * a^5 * b^4)

Since we have a common factor of a^5 both in the numerator and denominator, we can cancel it out:
-42 * b^3 / -315 * b^4

Thus, we are left with:
2 / (15b^2)

So, after correcting the original calculation, the simplified form of the expression is 2 / (15b^2).